2015
DOI: 10.1038/ncb3285
|View full text |Cite
|
Sign up to set email alerts
|

The centrosome is an actin-organizing centre

Abstract: Microtubules and actin filaments are the two main cytoskeleton networks supporting intracellular architecture and cell polarity. The centrosome nucleates and anchors microtubules and is therefore considered to be the main microtubule-organizing center. However, recurring, yet unexplained, observations have pointed towards a connection between the centrosome and actin filaments. Here we have used isolated centrosomes to demonstrate that the centrosome can directly promote actin filament assembly. A cloud of cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
243
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(279 citation statements)
references
References 68 publications
20
243
1
3
Order By: Relevance
“…In cells lacking Macf1, anchoring of microtubules around the basal body was disrupted. PCM1, a protein required for radial organization of microtubules at the basal body (Dammermann and Merdes, 2002; Farina et al, 2016), was also less dispersed in the absence of Macf1. Two other known direct binding partners of Macf1, EB1 and EB3, promote ciliogenesis via microtubule anchoring at the subdistal appendages, similar to the proposed mechanism for Macf1 (Schroder et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In cells lacking Macf1, anchoring of microtubules around the basal body was disrupted. PCM1, a protein required for radial organization of microtubules at the basal body (Dammermann and Merdes, 2002; Farina et al, 2016), was also less dispersed in the absence of Macf1. Two other known direct binding partners of Macf1, EB1 and EB3, promote ciliogenesis via microtubule anchoring at the subdistal appendages, similar to the proposed mechanism for Macf1 (Schroder et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The centrosome, consisting of two centrioles and surrounding pericentriolar material (PCM), is a microtubule- and microfilament-organizing center of animal cells (Farina, et al 2016). It regulates cell shape, polarity, migration, and the DNA-damage response and serves as a bustling hub of cellular signaling due to its ability to recruit and concentrate cell cycle, checkpoint, and signaling proteins and other molecules (Conduit, et al 2015; Lerit and Poulton 2015).…”
Section: An Overview Of Centrosome Abnormalitiesmentioning
confidence: 99%
“…Centrosomal F-actin was previously observed (Hubert et al, 2011), but it was not until recently that WASH was identified as the nucleation-promoting factor involved in its generation (Farina et al, 2015). Farina et al found that the accumulation of WASH on centrioles required pericentriolar material protein 1, MTs and dynein.…”
Section: Jmymentioning
confidence: 99%
“…Farina et al found that the accumulation of WASH on centrioles required pericentriolar material protein 1, MTs and dynein. Significantly, depletion of WASH impaired centrosomal F-actin nucleation (Farina et al, 2015). However, the mechanism by which WASH is activated at the centrosome, as well as the contribution of F-actin nucleation to centrosome architecture, positioning and organelle interaction, and the impact of F-actin on primary cilia formation and function remain to be determined.…”
Section: Jmymentioning
confidence: 99%